Validasi Modul Matematika Teknik Berbasis Mind Mapping - Nanndo Yannuansa; Jati Widyo L; Agung Widyo Samudra (Jurnal Pendidikan Matematika:Judika Education, 2020)
The purpose of this study was to see the mind mapping in terms of the quality of the material and media feasibility of validation by module experts. Expert validation is needed in module development so that the module is feasible or not used. Aspects that are validated are aspects of the module material including content, language, and media aspects of the module including presentation, and graphics. In looking at the quality aspect of the need analysis and validation of making a mind mapping based technique mathematics learning module by testing its feasibility before use. The validation analysis in the module uses methods from Crocker and Algina. The data instrument in this study was a validation questionnaire sheet. The results showed that the average feasibility aspect for the media was 89.79% and the material was 86.09, a total of 86.83%. In other words, the Mind mapping-based engineering mathematics module fulfilled the feasibility aspect. In conclusion, the Mind mapping-based engineering mathematics module developed is feasible in terms of media and module material. Keywords: Mathematical Techniques, Mind mapping, Modules, Validation